Tapping onto the Potential of Smartphone Applications for Psycho-Education and Early Intervention in Addictions - Zhang, Melvyn W. B.; Ho, Roger C. M. (Frontiers in Psychiatry, 2016)
E-health, and in particular smartphone based technology, is increasingly becoming commonplace in healthcare. Whilst psychiatry has tapped onto these innovations for conditions such as affective disorders as well as schizophrenia and psychosis, the usage of these technologies in addiction is limited. Addiction psychiatry could harness the potential of smartphone technologies. Given the increasing incidences of substance related problems globally, and along with the normalization of the general public’s perspectives towards substances, and also in consideration of unwillingness for at-risk individuals in seeking help, the authors hope to illustrate how these issues could potentially be solved using E-Health and technological innovations. The objectives of the current perspective article are to illustrate how recent advances in smartphone-based technologies could help in terms of psycho-education, as well as in helping individuals who are at-risk users in seeking help earlier. The authors aim to illustrate how the above are possible, building on existing theory driven framework that has been extensively reviewed in previous literature. Limitations with regards to the implementation of such technologies will also be discussed.